The effects of unaided augmentative and alternative communication interventions on communication in children with autism spectrum disorders : a scoping review - Dada, Shakila (University of Pretoria, 2024)
Mini Dissertation--(MAugmentative and Alternative Communication)--University of Pretoria, 2023.